Self-Request virginity testing: Attitudes and Approaches - Mehri Robatjazi; Mahmoud Abbasi (Mashhad University of Medical Sciences, 2020)
Introduction: Although virginity has been accepted as an undeniable value in most societies, however, self-request virginity testing is skeptical, so this review study was performed with aim to investigate the attitudes, approaches and consequences towards this test. Methods: In this review study, databases of SID, Iranmedex, Magiran , ProQuest, Pubmed, Ovide, ScienceDirect, EBSCO, MD Consult, Cochrane library, Scirus, Google scholar and WHO,UNFPA websites were searched by using the keywords of virginity testing, Self request, Ethical aspect since 1970-2018. The language for search was English and Persian. Results: Self-request virginity testing is generally done due to social and cultural pressures and has been criticized by many human rights associations following personal, social, and political consequence. The World Health Organization (WHO) has recognized it as violence against women. In Iran, virginity test is religiously prohibited (Haram), and self-request virginity testing is in contrary with providing services with respect and few clauses of Iranian patient's right charter. Self-request virginity testing is performed despite of all these mentioned. Conclusion: Virginity testingis more social outcome than being a medical examination, and along with the policies of WHO, not only virginity test is contrary with professional behaviors, Iran patients' rights charter, and Iranian constitute, but also it is prohibited according to Shiaat religious leaders. However, the dominant approach is a sort of negligence policy in this regard. According to the findings of this study, proper approach to virginity testing needs cooperation among responsible organizations and specialist in medical, judicial, law, religious, and social affairs.